A Late‐18th‐Century Merchantman Wrecked in the South Edinburgh Channel, Thames Estuary, England. (16th October 2012) - Parham, David; Rundell, Elizabeth; van der, Pieter
<x xml:space="preserve">Abstract</x> The South Edinburgh Channel wreck consists of the remains of a large, unidentified armed merchant ship whose cargo included a rare consignment of Swedish plate‐money, among other goods. The wreck was lost some time in the later part of the 18th century in the Thames Estuary and was uncovered briefly by natural means between 1972 and 1977. This allowed archaeological investigation, which was undertaken in very poor environmental conditions in the early days of maritime archaeology in the UK.